Flight patterns - White, Karen (Karen S.) (New York, New York : New American Library, 2016)
"The New York Times bestselling author of The Sound of Glass and coauthor of The Forgotten Room tells the story of a woman coming home to the family she left behind--and to the woman she always wanted to be.... Georgia Chambers has spent her life siftingthrough other people's pasts while trying to forget her own. But then her work as an expert on fine china--especially Limoges--requires her to return to the one place she swore she'd never revisit.... It has been thirteen years since Georgia left her family home on the coast of Florida, and nothing much has changed except that there are fewer oysters and more tourists. She finds solace in seeing her grandfather still toiling away in the apiary where she spent much of her childhood, but encountering her estranged mother and sister leaves her rattled. Seeing them after all this time makes Georgia realize that something has been missing--and unless she finds a way to heal these rifts, she will forever be living vicariously through other people's remnants. Toembrace her own life--mistakes and all--she will have to find the courage to confront the ghosts of her past and the secrets she was forced to keep..."--
Keywords: Families -- Fiction; Homecoming -- Fiction; Self-realization in women -- Fiction; Self-actualization (Psychology) in women -- Fiction; Domestic fiction; FICTION / Family Life; FICTION / Contemporary Women